Efficient NO2 sensing performance of a low-cost nanostructured sensor derived from molybdenite concentrate. Issue 20 (1st October 2020) - Hojamberdiev, Mirabbos; Goel, Neeraj; Kumar, Rahul; Kadirova, Zukhra C.; Kumar, Mahesh
Abstract : Molybdenite concentrate from the mining-metallurgy industry is characterized as a valuable material for the fabrication of an efficient and low-cost nanostructured gas sensor. Abstract : Accumulation of industrial solid waste necessitates the development of utilization processes and technologies to reduce their negative environmental impact. Herein, molybdenite concentrate from the mining-metallurgy industry is systematically characterized as a valuable starting material for the fabrication of an efficient and low-cost nanostructured gas sensor. Few-layer MoS2 is obtained from molybdenite concentrate by liquid nitrogen exfoliation and deposited on different substrates by spin coating and drop casting. It is found that spin coating is advantageous over drop casting in fabricating a homogeneous and dense few-layer MoS2 film. The charge-transfer-based sensing performance of the fabricated few-layer MoS2 film is investigated upon exposure to NO2 at different temperatures (50, 100, and 120 °C). At an optimized temperature of 120 °C, a faster recovery is achieved, and the fabricated device exhibits 28, 38, and 44% sensitivity to 10, 50, and 100 ppm NO2, respectively, making it suitable for practical applications. Furthermore, the adsorption affinity of NO2 to the predominant (002) crystallographic plane of MoS2 is estimated from the distribution of field density and the calculated differential adsorption energies. According to the molecular modeling data, NO2 in the Ar/NO2 mixture has better interaction (d E ad /d N NO2 = 4.77 kcal mol −1 ) with the few-layer MoS2 surface than individual NO2 (d E ad /d N NO2 = 2.57 kcal mol −1 ), and van der Waals interaction (≈14 kcal mol −1 ) is the main adsorption force compared to the relatively weaker electrostatic interaction (<1 kcal mol −1 ). This work demonstrates a straightforward approach not only for the conversion of molybdenite concentrate into an efficient and low-cost nanostructured gas sensor but also for the reduction of the negative impact of accumulated molybdenum concentrate on the environment and human health.